TO RECONSIDER THE “ACONTECERES”, TO RECONSIDER THE SPACES IN CHILE. - Onetto Pavez, Mauricio (Revista de Historia Social y de las Mentalidades, 2024)
The object of this article is to reflect on  the theoretical perspectives and main  lines of analyses that the editors of the  dossier had in mind in order to create this  project. The first part will focus on the  importance of the relationshihbetween  “space”, history and memory by generally  explaining the significance of this  correspondence for the topics of the  dossier. The second part will present the  main motivations that arise for studying  the Chilean case.
Keywords: Space constructions; memory; “infaust event”; continuities; ruptures; landscapes; catastrophe naturals